Hoima (Uganda) CSV Monitoring Summary 2018: CSA Adoption and perceived livelihoods and gender effects. - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Bejarano, Gustavo; Kakeeto, R; Recha, John W.M.; Ghebermihidin, A (2019)
This progress report summarizes the key results from the CSV monitoring undertaken in 2018 in the Hoima Climate-Smart village (Uganda). It focuses on the levels of CSA implementation and gender-disaggregated perceived effects of CSA practices on households livelihoods and gender dimensions